Penguatan Posyandu sebagai Pusat Edukasi Kesehatan Keluarga (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2026)
This community service program aims to strengthen the strategic role of Posyandu (Integrated Health Post) as a center for family health education through the innovation of its educational functions. Previously, Posyandu operations in the community tended to be limited to routine basic health services, such as weight monitoring and nutritional status recording, while the crucial aspect of health education remained suboptimal. This limitation has contributed to a lack of public understanding regarding healthy lifestyles and the prevention of chronic diseases or stunting. The methods implemented in this program included problem identification through observation, health socialization and education, specialized training for Posyandu cadres to enhance their communication capacity, and direct mentoring during activity implementation. The results demonstrated a significant increase in family knowledge regarding balanced nutrition and clean and healthy living behaviors (PHBS). Furthermore, Posyandu cadres became more active and skilled in delivering health information communicatively to the community. This program demonstrates that by strengthening its educational function, Posyandu can transform into an effective and sustainable family health learning center, significantly impacting the improvement of community health standards at the frontline level.